ELABORAÇÃO DE UM PRODUTO PANIFICÁVEL COM PROPRIEDADES FUNCIONAIS - Hermanns, Gislaine; Schmidt, Greici G.; Spies, Joseane T.; Schneider, Juliane; Hentz, Renata; Pompeo, Vanessa D. (Salão do Conhecimento, 2013)
Resumo